Facile fabrication of organobentonite-carboxymethyl chitosan hybrid film that absorbs organophosphate insecticides - Dau Hung Anh (2018)
© Indian Academy of Sciences. Organophosphate (OP)-insecticide-absorbing hybrid film containing 10% (w/w) organobentonite and carboxymethyl chitosan (CMCh) was fabricated and tested. Bentonite clay was modified to organobentonite by two steps modification with (1) NaCl and (2) plant alkaloid monovalent cation berberine. CMCh was synthesized from commercial shrimp chitosan. Afterwards, organobentonite was immobilized into CMCh matrix via in situ polymerization of CMCh to cast a hybrid film with 0.5 mm thickness. Scanning electron microscopy images of organobentonite powder and the film revealed the porous material and layer-upon-layer structure, respectively, which is supposed to enhance the water permeability of the film. Fourier transform infrared spectrometry analysis revealed similarly chemical characteristics of the CMCh component in the film and synthesizedCMChpolymer powder. The filmwas then investigated to remove four OP insecticides including profenofos, chlorpyrifos, methyl parathion and dimethoate of 5 ppm concentration in spiked water samples via batch filtration. High-pressure liquid chromatography analysis showed that the removal rates for profenofos, chlorpyrifos, methyl parathion and dimethoate after seven batches were 42, 39, 24 and 20%, respectively. Hence, absorptivity of this film for tested OP insecticides was demonstrated. Furthermore, the combination of organobentonite and natural chitosan is promising for novel absorptive film material generation with regard to environmental clean-up study.